Influence of Credit Limitations on the Growth of Small Enterprises in Fragile States: The case of Bosaso, Somalia (International Journal of Scientific Research and Management (IJSRM), 2024)
In recent years, the development of small enterprises has emerged as a vital component of economic growth and poverty alleviation in many countries. This study aimed to investigate the influence of credit limitations on the growth of Small Enterprises in Bosaso, Somalia. To achieve this objective primary data was collected and analyzed employing content analysis and multiple regression analysis. The study revealed that a majority of small enterprises in Bosaso have access to credit, with Microfinance Institutions (MFIs) and banks being the primary sources. However, a significant minority still lacks access to credit, mainly due to weak banking infrastructure and insufficient collateral. Small enterprises face numerous challenges when seeking loans, including insufficient guarantor, Political instability, limited financial infrastructure, high interest rates, and limited collateral. These challenges hinder their ability to access credit, limiting their growth potential. Also, the regression analysis indicated a positive and significant relationship between credit availability and small enterprise growth. Conversely, the access to loan and the cost of credit were found to have negative impacts on growth. On the other hand, Small Enterprises in Bosaso employ various coping strategies to overcome credit limitations, including informal financing, asset-based financing, diversification of income streams, cost reduction measures, and seeking grants or donor funding. Based on these findings, the authors made several recommendations to address the challenges and enhance the growth prospects of small enterprises in Bosaso, Somalia.